Construction Ethnoscience-Based Learning Environment Material in Scientific Knowledge - Asiyah; Sapri, Johanes; Novitasari, Naintyn; Saregar, Antomi; Topano, Adrian; Walid, Ahmad; Tamrin Kusumah, Raden Gamal (Journal of physics. Conference series, 2021)
The Indonesian 2013 curriculum does not specifically provide ethnoscience material in student handbooks. Therefore, the purpose of this study is to develop ethnoscience learning modules that are feasible and practical for use. The research method uses the Borg & Gall development model which consists of 8 stages, namely a preliminary study stage, a research planning stage, a design development stage, an initial trial phase, an initial product revision, a limited field test, a revised stage of the results of a limited field test, and a product stage end. This research is limited to the limited field trial stage namely the feasibility and practicality of the module. Data from the analysis of the questionnaire by calculating the percentage of achievement in each component of the percentage of achievement criteria of eligibility and practicality of science learning modules based on ethics that was developed. Ethnographic-based science learning modules developed were declared feasible to be used with a percentage of 92.00% (linguists), 76.25% (material experts), 86.25% (design/media experts) with the very feasible, feasible, and very feasible and the percentage of eligibility of 3 colleagues is 89.46%. From the results of these data, it can be concluded that the module has been feasible and practical to be used as teaching material in supporting the teaching and learning process on the material interaction of living things with their environment in junior high school 7 th grade.